2010
DOI: 10.1097/ypg.0b013e3283351209
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in SLC9A9 are associated with measures of Attention-deficit/hyperactivity disorder symptoms in families

Abstract: Objective A family was previously identified that cosegregates a pericentric inversion, inv(3)(p14 : q21), with an early-onset developmental condition, characterized by impulsive behavior and intellectual deficit. The inversion breakpoints lie within DOCK3 and SLC9A9 at the p-arm and q-arm, respectively. Based on this report, these genes were selected to be evaluated in a family-based attention-deficit/hyperactivity disorder (AD/HD) association study. Methods Conners’ Parent (CPRS) and Teacher (CTRS) Rating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 49 publications
(74 reference statements)
0
23
0
Order By: Relevance
“…We had hypothesised that we would see differences in social behaviour between phenotypes in this test, as Npas4 has been linked to neurodevelopmental disorders such as schizophrenia and autism in animal models of social, cognition and sensorimotor gating impairments [15] and of rearing in social isolation [37,38]. Npas4 has also been linked to attention-deficit hyperactivity disorder [39][40][41] and autism comorbid with epilepsy [42] in patient populations, through mutations affecting the SLC9A9 gene, a putative target of Npas4 [42]. However, the social behaviour of all genotypes was found to be normal, with all mice preferring to socialise in the first phase of the sociability test, and spend more time with the novel stranger mouse in the preference for social novelty stage.…”
Section: Discussionmentioning
confidence: 99%
“…We had hypothesised that we would see differences in social behaviour between phenotypes in this test, as Npas4 has been linked to neurodevelopmental disorders such as schizophrenia and autism in animal models of social, cognition and sensorimotor gating impairments [15] and of rearing in social isolation [37,38]. Npas4 has also been linked to attention-deficit hyperactivity disorder [39][40][41] and autism comorbid with epilepsy [42] in patient populations, through mutations affecting the SLC9A9 gene, a putative target of Npas4 [42]. However, the social behaviour of all genotypes was found to be normal, with all mice preferring to socialise in the first phase of the sociability test, and spend more time with the novel stranger mouse in the preference for social novelty stage.…”
Section: Discussionmentioning
confidence: 99%
“…It is not classified as an X-linked intellectual disability, but it does affect more males than females, with ratios ranging from 1:3 to 1:16, depending on country (Novik et al, 2006). Several genome wide association studies have suggested correlations between SLC9A9 and ADHD (Brookes et al, 2006; Lasky-Su et al, 2008; Markunas et al, 2010). NHE9 interacts with regulatory proteins at the intracellular C-terminal juxtamembrane domain (Zhang-James et al, 2011).…”
Section: Nhe9 and Intellectual Disabilitymentioning
confidence: 99%
“…By genetic approaches, NHE9 was linked to attention-deficit hyperactivity disorder (ADHD), addiction and mental retardation [37,102,153,109]. Several rare nonsense and missense mutations not found otherwise in asymptomatic individuals were described in affected patients.…”
Section: Slc9a9 -Nhe9mentioning
confidence: 99%